STRATEGI PENGELOLAAN KAWASAN RESTORASI EKOSISTEM SEMENANJUNG KAMPAR BERSAMA MASYARAKAT (Studi Kasus di IUPHHK-RE PT. The Best One Unitimber Kabupaten Pelalawan) - Bambang Dewo Bagus; Dibyo Kuswantoro; Burhanuddin Burhanuddin (Pelantar Press, 2024)
The objectives of this research are to describe and analyze land cover changes, peat swamp forest characteristics, social and economic community arround the consession as well as formulating a strategy for the management of the Kampar Peninsula ecosystem restoration area with the community. This research uses a mixed quantitative and qualitatve approach and is descriptive in nature. The survey method is used to obtain data from certain natural places by collecting data in the field and interviews. The data collected and analyzed are data on changes in land cover, characteristics of peat swamp forest (tree vegetation), social and economic conditions of the comminities around the concession and management of the ecosystem restoration area with the community. The results showed that there were three types of land cover in the IUPHHK-RE area of PT. The Best One Unitimber, namely secondary swamp forest, young regeneration forest and water bodies. There are 53 tree species (30 families) and 51 non-timber species. The dominant species in the secondary swamp forest land cover class from seedling to tree level were Block B Ketiau (Palaquium spp), Ketiau (Palaquium spp), Ketiau (Palaquium spp) and Kelat (Cantleya rubiginosa). Block Tobat Sembilan Kelat (Syzygium cf.cerinum), Kapas - kapas (Tetractomia tetrarandra), Kelat (Cantleya rubiginosa), Kelat (Cantleya rubiginosa) The species diversity index for all stands growth levels was moderate with a value of 2 for each Block B 2.83, 2.72, 3.12 and 2.98. Block Tobat Sembilan 2.73, 2.73, 3.07, 2.76. The majority of the villagers around the concession are ethnic Malays, there is community interaction with the ecosystem restoration area, namely fishermen in the Serkap River who come from Teluk Meranti Village and Pulau Muda Village. The recommended management strategy for ecosystem restoration areas is to prevent land conflicts by improving the community's economy through employment opportunities, business opportunities and partnership programs with local communities.